Characterizing the exposure of streams in southern Ontario to agricultural pesticides. (May 2022) - Raby, Melanie; Lissemore, Linda; Kaltenecker, Georgina; Beaton, Denise; Prosser, Ryan S.
Abstract: Aquatic communities can be exposed to pesticides transported from land. Characterizing this exposure is key to predicting potential toxic effects. In this study, samples of streamwater from 21 sites were used to characterize pesticide exposure to aquatic communities. Sites were in agricultural areas of southwestern Ontario, Canada and were sampled monthly from 2012 to 2019 from April to November. Samples were analyzed for a suite of hundreds of pesticides and pesticide degradation products and other water quality indicators (e.g., nutrients). Frequently detected pesticides included herbicides (2, 4-D; bentazon; MCPP; metolachlor) and neonicotinoid insecticides (NNIs) (clothianidin; thiamethoxam) which were detected in >50% of samples collected between 2015 and 2019. Non-metric multidimensional scaling (NMDS) was used to explore connections between pesticide concentrations and upstream land use and crop type. Detectable concentrations of the NNI clothianidin and many herbicides were related to corn, soybean, and grain/cereal crops while concentrations of the NNI imidacloprid, insecticide flonicamid, and fungicide boscalid were related to greenhouse/nursery land use. Potential toxicity to aquatic communities was assessed by comparing pesticide concentrations to Pesticide Toxicity Index (PTI) values. Few samples exceeded levels where acute (1% of samples) or chronic toxicity (10.5%) would be expected. The diamide insecticide chlorantraniliprole was detected in several streamwater samples at levels that may cause toxicity to aquatic invertebrates, highlighting the need for continued toxicity research into this pesticide class. The number of pesticides detected was positively correlated with nutrient and total suspended solids levels, underscoring the multiple stressors aquatic communities are exposed to in these habitats. Graphical abstract: Image 1 Highlights: Pesticides can transport to streams where aquatic communities may be exposed. Water samples from ≥18 streams were analyzed for pesticides from 2012 to 2019. Frequently detected pesticides included neonicotinoid insecticides and herbicides. Pesticides detected were related to upstream land use and crops. Hazard to aquatic communities was found to generally be low, with some exceptions.